2021
DOI: 10.3390/electrochem2030033
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Cu-Mn Films as Precursor Alloys for the Synthesis of Nanoporous Cu

Abstract: Cu-Mn alloy films are electrodeposited on Au substrates as precursor alloys for the synthesis of fine-structured nanoporous Cu structures. The alloys are deposited galvanostatically in a solution containing ammonium sulfate, (NH4)2SO4, which serves as a source of the ammine ligand that complexes with Cu, thereby decreasing the inherent standard reduction potential difference between Cu and Mn. The formation of the [Cu(NH3)n]2+ complex was confirmed by UV-Vis spectroscopic and voltammetric studies. Galvanostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Similar types of geometric features have been described in the literature before, for dealloyed CuMn. For example, Chen et al 28 identied nanocube and spheroid nanoparticles aer dealloying as Cu 2 O. Castillo et al 32 found that manganese oxide forms nanoplatelets during etching of electrodeposited CuMn which is supported by Biswal et al 57 who stated that MnO 2 can be electrodeposited from Mn 2+ in HCl by rst oxidation of Mn 2+ to Mn 3+ .…”
Section: Composition and Morphology Of The Porous Structurementioning
confidence: 96%
See 2 more Smart Citations
“…Similar types of geometric features have been described in the literature before, for dealloyed CuMn. For example, Chen et al 28 identied nanocube and spheroid nanoparticles aer dealloying as Cu 2 O. Castillo et al 32 found that manganese oxide forms nanoplatelets during etching of electrodeposited CuMn which is supported by Biswal et al 57 who stated that MnO 2 can be electrodeposited from Mn 2+ in HCl by rst oxidation of Mn 2+ to Mn 3+ .…”
Section: Composition and Morphology Of The Porous Structurementioning
confidence: 96%
“…The high chemical reactivity of both copper and manganese makes the (electro-)chemistry of these systems highly complex. For example, pronounced oxide formation of both alloy components has been reported 25,32 but a full understanding of the underlying kinetics is still missing. At the same time, deliberate control of oxide formation is of great importance for many applications including energy storage and sensing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation